2013
DOI: 10.7314/apjcp.2013.14.2.659
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Preserved Vegetables on Squamous Cell Carcinoma of Esophagus and Precancer Lesions in a High Risk Area

Abstract: Introduction: Squamous cell carcinoma of esophagus (ESCC) is one of the most common cancers in China. Preserved vegetables are processed foods and consumed in high amounts in the high risk areas for ESCC. This study aimed to investigate the relationships of preserved vegetable consumption with ESCC and precancer lesions. Methods: Cases from Yanting cancer hospital with pathological diagnosis of primary cancer, along with controls and individuals diagnosed with precancer lesions by endoscopy with iodine stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
4
11
0
Order By: Relevance
“…As a risk factor, under-nutrition includes low intake of fresh fruits and vegetables and low intake of micronutrients such as vitamin A, C, E, riboflavin, zinc and selenium. Studies have demonstrated a reduced risk of EC associated with regular intake of fresh fruits and vegetables with former to be more beneficial than latter (Yang et al, 2005;Yamaji et al, 2008;Mao et al, 2012;Song 2013). Same finding were observed over here.…”
Section: Discussionsupporting
confidence: 78%
“…As a risk factor, under-nutrition includes low intake of fresh fruits and vegetables and low intake of micronutrients such as vitamin A, C, E, riboflavin, zinc and selenium. Studies have demonstrated a reduced risk of EC associated with regular intake of fresh fruits and vegetables with former to be more beneficial than latter (Yang et al, 2005;Yamaji et al, 2008;Mao et al, 2012;Song 2013). Same finding were observed over here.…”
Section: Discussionsupporting
confidence: 78%
“…Preserved vegetable consumption was related to a higher risk of developing ESCC, which was consistent with the results of previous studies . Our results indicated that fruit consumption had a protective effect against developing ESCC, consistent with the results of previous studies .…”
Section: Discussionsupporting
confidence: 93%
“…Preserved vegetable consumption was related to a higher risk of developing ESCC, which was consistent with the results of previous studies. 16 Our results indicated that fruit consumption had a protective effect against developing ESCC, consistent with the results of previous studies. 17 A European prospective investigation into cancer and nutrition found that drinking tea was related to a reduced risk of developing ESCC, 18 and this protective association was consistent with the results of a systematic review (OR 0.46-0.64).…”
Section: Discussionsupporting
confidence: 92%
“…This study pointed out that the new risk factors, including smoking and high alcohol consumption, play a more important role (Lagergren et al, 2010;Amani et al, 2013). Thus, downward trends of ESCC in Luoyang might be attributed to the decreasing risks with socioeconomic level elevation and lifestyle modification, like intake of pickled or salted vegetables, preference for a high salt diet and prevalence of Helicobacter pylori infection (Xibin et al, 2002;Xibib et al, 2003;Kamangar et al, 2009;Lin et al, 2011;Song et al, 2013).…”
Section: Discussionmentioning
confidence: 94%